2008
DOI: 10.2169/internalmedicine.47.0519
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic Sporadic Dysferlinopathy Presenting with Elevation of Serum Creatine Kinase. Typical Distribution of Muscle Involvement Shown by MRI but not by CT

Abstract: We report an 18-year-old

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 13 publications
0
21
0
1
Order By: Relevance
“…The surprising finding from our study was the high frequency of muscle edema. Prior studies identified edema changes by means of MRI in a few dysferlinopathy cases . However, studies with large numbers of patients are limited, and the frequency of edema has varied greatly.…”
Section: Discussionmentioning
confidence: 99%
“…The surprising finding from our study was the high frequency of muscle edema. Prior studies identified edema changes by means of MRI in a few dysferlinopathy cases . However, studies with large numbers of patients are limited, and the frequency of edema has varied greatly.…”
Section: Discussionmentioning
confidence: 99%
“…Atypical patients who showed LGMD -Limb girdle muscular dystrophy, DACM -Distal anterior compartment myopathy. *Novel mutation, † Mutation is predicted as nonpathogenic using UMD predictor, ‡ Bioinformatics analyses predict no deleterious effect of the mutation, Gardner-Medwin and Walton scales: grade 0 -subclinical, hyperCKemia, and tolerance of normal activities, grade 1 -normal gait, unable to run freely, grade 2 -abnormal gait, grade 3 -muscle weakness, climbing stairs with support, grade 4 -positive Gower sign, grade 5 -unable to rise from floor, grade 6 -unable to climb stairs, grade 7 -unable to get up from chairs, grade 8 -unable to walk independently, grade 9 -unable to eat, drink, or sit without support, Disease progression was evaluated using three grades: S -slow progression, only 1 grade change during the past 5 years, M -moderate progression, 2 grade changes during the past 5 years R -rapid progression, 3 or more grade changes during the past 5 years exercise intolerance or asymptomatic hyper CPKemia without muscle weakness were reported before, [3,13,14] and they may be misdiagnosed as metabolic myopathy. However, the CPK level was constantly very high in patients with dysferlinopathies, while it was fluctuating in patients with metabolic myopathies.…”
Section: Discussionmentioning
confidence: 99%
“…) in the distal lower legs (gastrocnemius), or in the proximal thigh muscles (adductor magnus), followed by fatty degeneration . In an 18‐year‐old man with asymptomatic hyperCKemia, dysferlinopathy was diagnosed by the observation of muscle edema by MRI, while no change was found by CT scan …”
Section: Clinical Featuresmentioning
confidence: 99%